Sagittal Balance Using Position and Orientation of Each Vertebra in an Asymptomatic Population. Issue 16 (15th August 2022) - Gille, Olivier; Skalli, Wafa; Mathio, Paul; Kouyoumdjian, Pascal; Boishardy, Alice; Gajny, Laurent; Roscop, Cecile
Abstract : Study Design: A monocentric, retrospective radiographic study with 99 asymptomatic volunteers. Objective: The authors performed the postural analysis commonly scheduled when evaluating sagittal balance in a vertebra-by-vertebra manner by enrolling an asymptomatic population. They measured the position and angulation of each vertebra to reveal those for which the spatial positioning could be relevant during spinal surgeries. Summary of Background Data: Several recent publications detailed the sagittal alignment parameters and focus on global analysis parameters. Some patients with identical commonly evaluated spinal parameters have exhibited very different profiles, with notable differences in vertebral positions and orientations. Therefore, a fine segmental analysis of position of each vertebra could be interest to gain understanding of spine alignment. Materials and Methods: The authors obtained full-spine EOS x-rays of 99 volunteers in the standard free-standing position. We used a validated three-dimensional reconstruction technique to extract current spinal parameters and the positions and angulations of all vertebrae and lumbar discs. Particular attention was paid to the positions and angulations of the apical and transitional vertebrae in the general population and in subgroups according to pelvic incidence (PI). Results: T1 was the most common transitional cervicothoracic vertebra (in 89.9% of subjects) and was oriented downwards by an average of 22.0° (SD=7.3°, minimum=2.3°, maximum=40.1°). The thoracic apex trio of T5 (22.2%), T6 (28.3%), and T7 (36.4%) were equally found. The transitional thoracolumbar vertebrae were L1 (39.4%) and T12 (33.3%). The lumbar apex was usually the L3-L4 disc (36.4%). T1 seemed to be the transitional vertebra (90%) irrespective of the PI. For the other relevant vertebrae, the greater the PI, the more cranial the vertebra. Conclusions: We performed a detailed three-dimensional assessment of overall spinal balance using positional and rotational parameters. The positions and orientations of all vertebrae were specified, particularly the apical and transitional vertebrae. Level of Evidence: Level 3.